Endoscopic Microvascular Decompression with Transposition for Trigeminal Neuralgia and Hemifacial Spasm: Technical Note - Komatsu, Fuminari; Imai, Masaaki; Hirayama, Akihiro; Hotta, Kazuko; Hayashi, Naokazu; Oda, Shinri; Shimoda, Masami; Matsumae, Mitsunori (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
Background Endoscopic microvascular decompression (MVD) offers reliable identification of neurovascular conflicts under superb illumination, and it provides minimally invasive surgery for trigeminal neuralgia and hemifacial spasm. Transposition techniques have been reported as a decompression method to prevent adhesion and granuloma formation around decompression sites, providing better surgical outcomes. The feasibility and effects of transposition under endoscopic MVD were evaluated.Material and Methods Fully endoscopic MVD was performed using 4-mm 0- and 30-degree endoscopes. The endoscope was fixed with a pneumatic holding system, and a bimanual technique using single-shaft instruments was performed. Transposition was performed with Teflon felt string and fibrin glue. Surgical results were evaluated using the scoring system proposed by Kondo et al.Results The endoscope was introduced via a retrosigmoid keyhole. The 0-degree endoscope was advanced through the lateral aspect of the cerebellar tentorial surface to the trigeminal nerve in cases of trigeminal neuralgia and through the petrosal surface of the cerebellum to the facial nerve in cases of hemifacial spasm. Neurovascular conflicts and perforators from the offending artery were clearly demonstrated under the 30-degree endoscopic view, and transposition of the offending artery was safely performed with preservation of perforators. Clinical symptoms improved without permanent complications.Conclusion Endoscopic MVD with the transposition technique is feasible. Superb endoscopic views demonstrate perforators arising from the offending artery behind the corner, allowing damage to perforators to be avoided during the transposition technique. Endoscopic MVD using the transposition technique is expected to offer excellent surgical results.
Keywords: endoscopic keyhole surgery; posterior skull base; retrosigmoid approach; root entry/exit zone